IMPLEMENTASI GOOD GOVERNANCE MELALUI REFORMASI SISTEM KEPEGAWAIAN - Muhamad Adian Firnas (Jurnal Manajemen Kepegawaian, 2007)
In the 1980s, China began to implement a civil service to establish a market-oriented economy and foster reform of the politico-administrative system. The Modern civil service system in China began by contructing a legal framework and drafting general regulation to stipulate and enforce conditions about personnel and administrative system. More than eight years have passed since China officially instituted the civil service system on October 1, 1993. Design to promote socialism in China, the civil service is also intended to act in the broader interests of social advancement. On the one hand, the modern civil service in China has been hampered by the need to reform the traditional cadre system; on the other, the development of market-oriented economy has created conditions advantageous to its development. As it continues to develop and improve, the new admininistrative-personnel management system has demonstrated its advantages over the previous system both in theory and in practice.